2019
DOI: 10.2147/cmar.s223204
|View full text |Cite
|
Sign up to set email alerts
|

<p>Current Understanding of Circular RNAs in Gastric Cancer</p>

Abstract: Gastric cancer (GC) is the third most common cause of cancer-related death worldwide. Advanced diagnosis and high rates of relapse and metastasis are associated with the poor prognosis of this disease. GC has a complex etiopathogenesis of which the underlying mechanisms remain to be explored. Studies on circular RNAs (circRNAs), noncoding RNAs that may be potential targets in GC, have made substantial progress over the past few years. CircRNAs exert important effects on the onset and progression of GC. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 106 publications
1
16
0
Order By: Relevance
“…More studies on alternative splicing during the transcription of hsa_circ_0085576 or its coding gene ASAP1, might be carried out to illustrate the regulatory mechanism. In addition, the diagnostic performance of circRNA has been reported in gastric cancer [33], cervical cancer [34], and even acute kidney injury [35]. Our results showed hsa_circ_0085576 may serve as a prognosis marker.…”
Section: Discussionsupporting
confidence: 54%
“…More studies on alternative splicing during the transcription of hsa_circ_0085576 or its coding gene ASAP1, might be carried out to illustrate the regulatory mechanism. In addition, the diagnostic performance of circRNA has been reported in gastric cancer [33], cervical cancer [34], and even acute kidney injury [35]. Our results showed hsa_circ_0085576 may serve as a prognosis marker.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, accumulating evidence has indicated that circular RNAs (circRNAs) with covalent closed-loop structures exert a vital regulatory effect on the occurrence and development of various cancers. 4 Abnormally expressed circRNAs in GC have been found to mediate tumor progression by regulating microRNAs: 5 for example, circ-RanGAP1 accelerated tumor metastasis in GC through a miR-877-3p/VEGFA regulatory axis. 6 Circ-PVT1 enhanced the resistance of GC cells to paclitaxel via down-regulating miR-124-3p and elevating ZEB1.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput sequencing, the roles of circular RNA (circRNA) have been adequately identified in GC. 7 , 8 circRNAs are generated from precursor mRNAs (pre-mRNAs) through back-splicing. Evidence has revealed the biogenesis of circRNAs in eukaryocytes, including splicing factor, eukaryotic initiation factor, and N 6 -methyladenosine (m 6 A).…”
Section: Introductionmentioning
confidence: 99%